Functional Phenotypic Diversity of Regulatory T Cells Remaining in Inflamed Skin - Ikebuchi, Ryoyo; Fujimoto, Maika; Nakanishi, Yasutaka; Okuyama, Hiromi; Moriya, Taiki; Kusumoto, Yutaka; Tomura, Michio (Frontiers in Immunology, 2019)
Regulatory T cells (Tregs) migrate between lymphoid and peripheral tissues for maintaining immune homeostasis. Tissue-specific function and functional heterogeneity of Tregs have been suggested, however, correlation between them and inter-tissue movement remain unknown. We used a contact hypersensitivity model of mice expressing a photoconvertible protein for tracking migratory cells. After marking cells in skin, we purified Tregs exhibiting a different migration pattern [Tregs recruiting to or remaining in the skin and emigrating from the skin to draining lymph nodes (dLNs) within half a day] and examined single-cell gene and protein expression profiles. Correlation and unsupervised clustering analyses revealed that Tregs in both skin and dLNs comprised two subpopulations, one highly expressing Nrp1 with variable CD25, Granzyme B, and/or CTLA-4 expression and another with 3 subsets strongly expressing CD25, Granzyme B, or CTLA-4 together with CD39. Characteristic subsets of Tregs remaining in the skin displayed higher CD25 and CD39 expression and lower Granzyme B and CTLA-4 expression compared with Tregs migrating to the skin. In addition, CCR5 expression in Tregs in skin was positively and negatively correlated with CD39 and Nrp-1 expression, respectively. To assess the predictive value of these data for immunotherapy, we blocked CCR5 signaling and found modest downregulation of CD39 and modest upregulation of Nrp1 expression in skin Tregs. Our data reveal a high functional diversity of Tregs in skin that is strongly related to trafficking behavior, particularly skin retention. Modulation of tissue-specific trafficking and function is a promising clinical strategy against autoimmune, infectious, and neoplastic diseases.